Strategi Pengembangan Batik Kujur Berbasis Ekonomi Kreatif di Tanjung Enim Kab. Muara Enim Sumatera Selatan - Solihan Solihan; Maya Panorama; Ali Mursyi Abdul Rasyid (Ekonomis: Journal of Economics and Business, 2022)
This study aims to explore kujur batik craftsmen as one of the potential strengths of local economic development in Tanjung Enim Village, Muara Enim Regency, South Sumatra, analyze the obstacles faced by kujur batik craftsmen in developing the batik art craft industry and analyze the contribution of kujur batik production in strengthening the economy. local in Tanjung Enim Village. This research is a descriptive research with a qualitative approach. Data were collected by means of field observations, interviews, and documentation methods. To obtain the validity of the data, the source triangulation technique was used. Data were analyzed using interactive analysis techniques and supply-demand analysis. This research is expected to provide benefits to all parties involved, in order to support the development of batik kujur based on a creative economy to support economic improvement in the Tanjung Enim community. The strategy for developing kujur batik is based on creative economy by exploring the potential for creation, innovation, housewives and teenagers by creating batik creations with local characteristics of kujur motifs, by adding new creative motifs characterized by the region. This batik industry can increase the income of housewives and teenagers in Tanjung Enim Village